One step activation using potassium hydroxide on prepared activated carbon for base transesterification reaction - Muda, Nor Wajihan (2015)
Palm kernel shell is an abundant solid waste from palm oil processing mills in tropical countries like Malaysia and Indonesia. The utilization of these agricultural wastes in production of activated carbon will greatly help overcoming environmental issue economically. In this study, activated carbon from palm kernel shell via one-step activation with potassium (AC/KOH) was successfully prepared. The activated carbon has been prepared using different percentage concentrations of KOH and carbonized at 600oC for 2 h. All the prepared AC/KOHs were characterized using Fourier Transformed Infrared (FTIR), Nitrogen Adsorption Analysis, Field Emission Scanning Electron Microscope (FESEM), X-ray Powder Diffraction (XRD) and X-ray Fluorescence (XRF). The soluble basicity and the basic strength of the prepared AC/KOHs were determined using back titration and Carbon Dioxide Temperature Program Desorption (CO2-TPD). FTIR analysis of the raw palm kernel shell showed the presence of various functional groups. However, after the activation and carbonization, most of the functional groups were eliminated. A high BET surface area of 1054 m2/g was obtained from 10% AC/KOH, while the BET surface area for 15%, 20% and 25% AC/KOH decreased probably due to KOH residue or the collapse of the pore walls, which blocked the pores. From the basicity analysis, when the percentage of KOH concentrations increases, the basicity of the AC/KOH was also increased. The prepared AC/KOH was then used as a heterogeneous base catalyst for transesterification of palm oil and dimethyl carbonate (DMC). Dimethyl carbonate was selected to replace alcohol to prevent the leaching of KOH into the biodiesel. Besides that, the used of DMC in transesterification produced glycerol free-fatty acid methyl ester (FAME). Analysis and determination of biodiesel production were performed using Gas Chromatography–Flame Ionization Detector (GC-FID) and Gas Chromatography-Mass Spectrometer (GC-MS). Increased percentage concentrations of potassium in AC/KOH made a significant impact on the conversion of palm oil to biodiesel. The percentage conversion of biodiesel for 10% AC/KOH, 15% AC/KOH, 20% AC/KOH and 25% AC/KOH calculated about 35%, 45%, 63% and 67%, respectively. Thus, it can be concluded that the AC/KOH can be used as a catalyst in biodiesel production.